Peningkatan Berpikir Kritis dan Gaya Belajar Menggunakan Discovery Outdoor Learning Peserta Didik SMAN 10 Batanghari: Improvement of Critical Thinking and Learning Style Using Discovery Outdoor Learning Participants SMAN 10 Batanghari - Mardesta Fazania; Revis Asra; Upik Yelianti (Universitas Jambi, 2019)
Students still have difficulty understanding plant material because they tend to memorize and do not understand the meaning of the learned materials. This study aims to determine the application of discovery learning outside the classroom to improve critical thinking skills, learning styles, attitudes, scientific activities, and a better learning biology atmosphere. This Classroom Action Research (CAR) consists of three cycles involving students of class X MIA 2 SMAN 10 Batanghari. The instruments used were observation sheets, tests, questionnaires, and documentation. Critical thinking skills, critical thinking attitudes, and scientific activities, in general, are increasing from cycle I to cycle III. In the aspect of learning style, the number of students using visual learning styles and auditory learning styles has increased from cycle I to cycle III. In contrast, the number of students using kinesthetic learning styles has decreased over the cycles. The use of outdoor learning by utilizing urban forests and school gardens creates a comfortable and pleasant learning atmosphere. Students are motivated to be actively involved; they can maximize attitudes, scientific activities, critical thinking skills, and learning styles in the learning process.